Fabrication of Mucoadhesive Films Containing Pharmaceutical Ionic Liquid and Eudragit Polymer Using Pressure-Assisted Microsyringe-Type 3D Printer for Treating Oral Mucositis - Tatsuaki Tagami; Maya Okamura; Koki Ogawa; Tetsuya Ozeki (Pharmaceutics, 2022)
Oral mucositis in the oral cavity, caused by radiation therapy and chemotherapy, requires personalized care and therapy due to variations in the lesions of patients. In the present study, we fabricated a model of personalized oral film containing an ibuprofen/lidocaine ionic liquid (IL) for patients with oral mucositis using a pressure-assisted microsyringe-type 3D printer at room temperature. The film contained a Eudragit polymer (L100, EPO, or RSPO) to make the film solid, and the printer ink was composed of organo ink (organic solvent to dissolve both drugs and the Eudragit polymer). The viscosity of the printer ink was assessed to investigate its extrudability. The contact angle and the surface tension at the interface between each liquid printer ink and a solid polypropylene sheet were measured to determine the retention of the ink in 3D printing. The physical properties of IL-loaded Eudragit-based dry films were examined by X-ray diffraction and differential scanning calorimetry. Dissolution tests indicated that IL-loaded films containing a Eudragit polymer exhibited different drug release rates in phosphate buffer (pH 6.8; Eudragit L100 > IL alone > Eudragit EPO > Eudragit RSPO). These results provide useful information for the specific fabrication of IL-loaded polymer-based films using organo inks and pressure-assisted microsyringe-type 3D printers.